Plant Species Inventory at SMP Negeri 2 Lakea, Buol Regency, and Their Utilization as Learning Media - Nurhidayah; Musdalifa Nurdin; Lilies; Aan Febriawan; Vita Indri Febriani; Lestari M.P. Alibasyah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to identify and describe the plant species found on the grounds of SMP Negeri 2 Lakea, Buol Regency, and to develop a digital pocketbook in flipbook format as a contextual learning medium based on local biological resources. An exploratory descriptive method was employed, combining qualitative analysis for plant identification with descriptive quantitative analysis for media validation. Data were collected through surveys and systematic field exploration, direct observation, documentation, and plant identification based on morphological characteristics using relevant literature. The developed medium was validated by content, media, and instructional design experts and evaluated through responses from 30 seventh-grade students at SMP Negeri 2 Lakea. The study identified 35 plant species belonging to 20 families and representing four growth forms: herbs, shrubs, bushes, and trees. The recorded species included ornamental, medicinal, and shade plants, as well as naturally occurring wild species. These findings indicate that the school environment has substantial biological resource potential that can be utilized as a contextual learning resource. Based on student responses, the digital pocketbook was considered practical, concise, interactive, and helpful for understanding the learning material. The feasibility assessment yielded scores of 80% from the content expert, 83% from the media expert, 87% from the design expert, and 91% from student responses. The overall mean score was 85%, placing the medium in the highly feasible category. Therefore, the digital pocketbook based on plant diversity at SMP Negeri 2 Lakea is suitable for use as a contextual learning medium integrating local biological potential.